STUDI LITERATUR PEMBIAYAAN UMKM PADA PERBANKAN SYARIAH - Nurhikmah Berasa; Haya Aghnia Azzahra; Muhammad Habib Rifky; Muhammad Ikhsan Harahap (CV. Barokah Publsiher, 2025)
This study aims to analyze the role and effectiveness of Islamic banking in financing micro, small, and medium enterprises (MSMEs) in Indonesia. Using a qualitative descriptive approach through literature review, this research synthesizes data from books, scientific journals, and official publications from 2014 to 2024 related to Islamic banking and MSME development. The study reveals that Islamic banks play a crucial role in supporting MSMEs through profit-and-loss sharing schemes such as mudharabah, musyarakah, and murabahah, which emphasize fairness and partnership principles. Despite these advantages, several obstacles remain, including low Islamic financial literacy, limited collateral, and insufficient product innovation for micro-segments. The findings suggest that collaboration among Islamic banks, government, and financial technology institutions is necessary to enhance inclusion and innovation in Islamic financing. This research contributes theoretically to the development of Islamic financial models for MSMEs and provides practical implications for policymakers to strengthen the Islamic banking ecosystem in promoting inclusive and sustainable economic growth in Indonesia.